If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (K + 2)(6k + -7) = 0 Reorder the terms: (2 + K)(6k + -7) = 0 Reorder the terms: (2 + K)(-7 + 6k) = 0 Multiply (2 + K) * (-7 + 6k) (2(-7 + 6k) + K(-7 + 6k)) = 0 ((-7 * 2 + 6k * 2) + K(-7 + 6k)) = 0 ((-14 + 12k) + K(-7 + 6k)) = 0 (-14 + 12k + (-7 * K + 6k * K)) = 0 (-14 + 12k + (-7K + 6kK)) = 0 Reorder the terms: (-14 + -7K + 12k + 6kK) = 0 (-14 + -7K + 12k + 6kK) = 0 Solving -14 + -7K + 12k + 6kK = 0 Solving for variable 'K'. Move all terms containing K to the left, all other terms to the right. Add '14' to each side of the equation. -14 + -7K + 12k + 14 + 6kK = 0 + 14 Reorder the terms: -14 + 14 + -7K + 12k + 6kK = 0 + 14 Combine like terms: -14 + 14 = 0 0 + -7K + 12k + 6kK = 0 + 14 -7K + 12k + 6kK = 0 + 14 Combine like terms: 0 + 14 = 14 -7K + 12k + 6kK = 14 Add '-12k' to each side of the equation. -7K + 12k + -12k + 6kK = 14 + -12k Combine like terms: 12k + -12k = 0 -7K + 0 + 6kK = 14 + -12k -7K + 6kK = 14 + -12k Reorder the terms: -14 + -7K + 12k + 6kK = 14 + -12k + -14 + 12k Reorder the terms: -14 + -7K + 12k + 6kK = 14 + -14 + -12k + 12k Combine like terms: 14 + -14 = 0 -14 + -7K + 12k + 6kK = 0 + -12k + 12k -14 + -7K + 12k + 6kK = -12k + 12k Combine like terms: -12k + 12k = 0 -14 + -7K + 12k + 6kK = 0 The solution to this equation could not be determined.
| x=ax+1a+bx-2b | | 12-3x+9x=14+6x | | 5x^2+4xy+2y^2=6 | | 3d-274d+10c=120 | | 2x=17x+15 | | 11x+61=Ax+Bx+5A+8B | | 6-2y=10-8y+6y | | x-22x+2y=4 | | 11x+61=Ax+Bx+5A+8A | | (x-2)2x+2y=4 | | (-8)-14= | | 6g-4h=-2g+28 | | 2m-7n-4m+9n= | | 5p+8m=-10p+3 | | 4x-8y=2x+10 | | 8-n(2)=20 | | 81-x^4=0 | | 5N^3+2N^2+15N=0 | | 10+x-(2-3x)=4 | | 1080=26x+95 | | 2t+1=-1 | | 26x+95=1080 | | 7(x+1)+6=4x+3(4+x) | | x+8=-1 | | X^2-(32+2i)x+62i=0 | | 2y+5y=35 | | 7X+3=3X-7 | | 2b-3d-3b+6d= | | -5+4x=7 | | 7=6n-5 | | 4x+-3=-5x+6 | | n^2+4n=21 |